2014
DOI: 10.1007/s12288-013-0326-4
|View full text |Cite
|
Sign up to set email alerts
|

AML M7 Misdiagnosed as ALL

Abstract: Hematogones, which are normal precursors of B lymphocytes in the bone marrow, may be mistaken for blast cells on flow cytometry and histology when their numbers increase. We report such a case in a 16 months old male who was unsuccessfully treated for a pre-B cell ALL on the basis of flow cytometry of the bone marrow which showed a substantial population of CD19 and CD10 expressing 'blast' cells. A diagnosis of AML M7 was made on a subsequent bone marrow biopsy in which the blast cells expressed CD61 and Facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Besides the small sized blasts can be seen in T-ALL or acute megakaryocytic leukemia (AML-M7) therefore indistinguishable morphologically. 7,8 Also one would argue that if the Blasts show PAS positivity, then the diagnosis goes in favour of ALL. But due to a poor sensitivity and not so reliable specificity, the PAS stain on cytochemistry cannot be considered for lineage assignment for ALL unlike MPO or NSE, which are considered as lineage specific markers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the small sized blasts can be seen in T-ALL or acute megakaryocytic leukemia (AML-M7) therefore indistinguishable morphologically. 7,8 Also one would argue that if the Blasts show PAS positivity, then the diagnosis goes in favour of ALL. But due to a poor sensitivity and not so reliable specificity, the PAS stain on cytochemistry cannot be considered for lineage assignment for ALL unlike MPO or NSE, which are considered as lineage specific markers.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive analysis of literature was done from 1994-2020 and three authors [3][4][5] have reported similar hindrance in the diagnosis of acute megakaryoblastic leukaemia because of presence of hematogones. Anton-Harisi et al [4] reported 2 cases where there was either preferential uptake of hematogones owing to marrow fibrosis or there was dry tap and flowcytometry was repeatedly inconclusive.…”
Section: Cd33 Hla-dr Cd123 Cd4 Cd7 Positivementioning
confidence: 99%
“…Repeated bone marrow aspirations were done to arrive at final diagnosis delaying the treatment. In a case study by Chaudhari et al [5] diagnosis of pre-B ALL was mistakenly made on flowcytometry when patient was not responding to chemotherapy, repeat aspirate and biopsy were done. On immunohistochemistry the blasts were positive for CD61, factor VIII, CD117 and HLADR and final diagnosis of acute megakaryocytic leukaemia was reported.…”
Section: Cd33 Hla-dr Cd123 Cd4 Cd7 Positivementioning
confidence: 99%